Comparison of Remimazolam Tosilate and Etomidate on Hemodynamics in Cardiac Surgery: A Randomised Controlled Trial - Hu B; Zhang M; Wu Z; Zhang X; Zou X; Tan L; Song T; Li X (Dove Medical Press, 2023)
Bailong Hu,1,2,* Mei Zhang,2,* Zhen Wu,2,* Xiaoyuan Zhang,2,* Xiaohua Zou,1,2 Li Tan,1 Tao Song,1 Xingyu Li1 1Department of Anesthesiology, The Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou Province, People's Republic of China; 2College of Anesthesiology, Guizhou Medical University, Guiyang, Guizhou Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaohua Zou, Email zouxiaohuazxh@163.comBackground: Remimazolam tosilate (RT) is a new ultrashort-acting γ-aminobutyric acid subtype A (GABAA) agonist, with the characteristics of rapid onset and offset, minimal cardiorespiratory depression. Currently, few studies have compared the effect of RT and etomidate on hemodynamics during anesthesia induction. Here, we aimed to compare the hemodynamic effects of different doses of RT and etomidate for anesthesia induction in patients undergoing cardiac surgeries.Methods: Patients were recruited from January to September 2022 in this single-center, prospective, randomized, double-blind trial. A total of 117 patients undergoing selective valve replacement surgery were randomly divided into low-dose RT (0.2 mg/kg) group (group LR), high-dose RT (0.3 mg/kg) group (group HR), or etomidate (1.5 mg/kg) group (group E), respectively. The primary outcome was hemodynamic fluctuations (mean arterial pressure fluctuation value [∆MAP]; heart rate fluctuation value [∆HR]) during anesthesia induction. Secondary outcomes included the incidence of adverse drug reactions (injection pain and myoclonus) and adverse cardiovascular events, vital signs at different time points and the cumulative doses of vasoactive drugs.Results: The hemodynamic fluctuations (∆MAP) in group LR and group E were significantly lower than that in group HR. In addition, the incidence of hypotension and the cumulative norepinephrine doses in group E and group LR were also significantly lower than that in group HR. Furthermore, the incidence of injection pain and myoclonus in group LR and group HR were less frequently recorded compared with group E. There were no significant differences in terms of ∆HR, tachycardia, hypertension, severe bradycardia, vital signs at different time points, lactic acid and blood glucose between both groups.Conclusion: Compared with etomidate, low-dose RT (0.2mg/kg) can not only provide stable hemodynamic parameters but also cause fewer adverse reactions when used for anesthesia induction in patients with cardiac disease.Keywords: remimazolam tosilate, etomidate, hemodynamics, cardiac surgery